PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN ECENG GONDOK DI DESA KEBONDOWO KECAMATAN BANYUBIRU KABUPATEN SEMARANG - Syarifatus Sa’diyah, Ismi; Maesaroh, Maesaroh; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The Kebondowo Village Government has carried out community empowerment through the use of water hyacinth for its community with the aim of improving the standard of living of the people of Kebondowo Village by utilizing the potential that exists in Kebondowo Village, namely Water Hyacinth, more optimally. This research aims to analyze community empowerment through the use of water hyacinth in Kebondowo Village and analyze the driving and inhibiting factors in community empowerment through the use of water hyacinth in Kebondowo Village. The method used is a descriptive qualitative method. Data collection techniques through interviews, observation, documentation and literature study. The results of the findings are that at the awareness and behavior formation stage there is an increase in awareness and willingness of the community to utilize water hyacinth, at the transformation stage the ability increases the skills of the Kebondowo Village community in terms of utilizing water hyacinth, at the intellectual enhancement stage there are results in the form of increasing the community's ability by being taught skills in how to finish products, only However, people have not been given knowledge about marketing methods so that people cannot independently sell their products. The driving factors for empowerment are natural resources and human resources. Factors inhibiting empowerment include limited managerial abilities and limited business capital. The recommendation of this research is to carry out retraining and mentoring by providing more diverse skills, apart from that the Kebondowo Village Government can form an empowerment task force to carry out regular control and monitoring.